Modernist irony and racial-cultural difference: the case of E. M. Forster - Khalid Hadeed (Cogent Arts & Humanities)
Among the qualities that distinguish E. M. Forster’s literary legacy is his dexterous use of irony to critique norms and ideologies that call for conformism at the expense of an authentic experience of life. When approached as a tool of social critique, Forster’s irony might be said to possess a high degree of critical intelligence. However, as demonstrated by Alan Wilde, the purposiveness in Forster’s irony becomes more uncertain as he progresses in his literary career, reflecting a growing modernist doubt in the ability of life, relationships, and language to contain and sustain universally valid expressions of meaning and value. In this paper, I will compare the novels Where Angels Fear to Tread (1905) and A Passage to India (1924) to argue that anxious experiences of racial-cultural difference, in transnational and colonial contexts, are significantly responsible for the disorientation of purpose in Forster’s modernist irony. Through this argument, I demonstrate that a fuller understanding of modernist irony, particularly as a mode of alienated consciousness, requires investigating its relationship with historically contingent and geopolitically significant constructions and representations of racial-cultural difference.